Construction claims & responses : effective writing & presentation - Hewitt, Andy (writer on construction claims) (Ames, Iowa : Wiley-Blackwell, 2011)
Featuring a Foreword by Roger Knowles FRICS, FCIArb, FQSi, Barrister The book discusses the different types of claim common to construction contracts and presents a step-by-step guide which demonstrates the process of building up the submission of a claim. It includes guidelines as to how to set out the claim, section by section in a logical manner to ensure that the essentials of a successful claim are included. Worked examples of claims for variations, extensions of time and additional payment are included together with sample wording showing precisely how the claim may be presented in a ma.
Introduction -- Types of claim -- Presentation -- The essential elements of a successful claim -- The preliminaries to the claim -- The extension of time claim -- The claim for additional payment -- The appendices and editing -- Claim responses and determinations -- A note on dispute review boards.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: FIDIC forms of contract; Construction contracts; Claims; LAW -- Military; Claims; Construction contracts